ASEAN-CHINA FREE TRADE AGREEMENT: TANTANGAN DAN PELUANG BAGI INDONESIA - Latif Adam; Siwage Dharma Negara (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2010)
The Free trade agreement between ASEAN and China will have a significant impact on the Indonesian economy. Many observers predicted that Indonesia will be flooded by cheap import products from China after the implementation of ACFTA. This in turn will worsen Indonesias trade deficit against China. Fear about the negative impacts of ACFTA were raised by most businessmen, citing about various obstacles that detriment their competitiveness including lack of infrastructure, cumbersome bureaucracy, poor law enforcement, corruption, etc. Inevitably, the implementation of ACFTA without sufficient support from the government will put the local industry and small businesses at risk of bankruptcy. There is also prediction that Indonesia will become more dependent on export of natural resources and agricultural based product groups, such as oil and gas, coal, palm oil, and rubber. On the contrary, many manufacturing industries, including textile, garment, electronics, food, steel/iron, and horticultural products, are predicted to be negatively affected by the implementation of ACFTA. This paper discusses about the challenges and opportunities faced by Indonesia in the wake of ACFTA implementation. The main message is that Indonesia needs to put more serious efforts in order to become a leveled trade partner with China. Indonesia needs to improve its technological and managerial capabilities and try to connect itself into global production network, in which China becomes the system integrator.consciousness.Keywords: ACFTA, neraca perdagangan, ekspor impor, daya saing